Relevance of Criminal Law Formulation in the Law of Domestic Violence Elimination in Indonesia - Setyowati, Dewi; Rusdiana, Emmilia (Universitas Negeri Semarang, 2020)
Violence Against Women is becoming more and more with specific domestic violence, as well as the cause hidden behind divorce. The issue of domestic violence is arranged by The Law Number 23 of 2004 on The Elimination of Domestic Violence which contains a summary of criminal act in Article 44 to Article 53. This study attempts to analyze the philosophy of regulation of domestic violence in Indonesia and the political law of the law number 23 Year 2004 on the elimination of domestic violence is related to the principles in the formulation of criminal law. This research is a normative legal research, and was obtained by studying documentation, discussion, and literature study and with collection data is literature study and analyzed prescriptively. The authors believe that the household paradigm that is in accordance with the objectives of this law is to realize the integrity of households, and it implies the formulation of criminal law is not appropriate, so it is a manifestation of overcriminalization/ penalization.